2019
DOI: 10.1007/s00520-019-05203-3
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity in patients with cancer: self-report versus accelerometer assessments

Abstract: Purpose The level of daily physical activity in patients with cancer is frequently assessed by questionnaires, such as the Physical Activity Scale for the Elderly (PASE). Objective assessments, with for example accelerometers, may be a good alternative. The aim of this study was to investigate the agreement between the PASE questionnaire and accelerometer-assessed physical activity in a large group of patients with different types of cancer. Methods Baseline accelerometer and PASE questionnaire data of 403 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 44 publications
1
26
1
Order By: Relevance
“…No differences in PA were found for tumor stage, pain level or worry and depression (Table 4). Although, the Dutch study did observe an association between PA and tumor stage, 7 another study in HNC patients found an association between PA and fatigue but not with depression 12 . QoL has generally been associated with PA in HNC, but the different aspects of QoL are more or less associated 36 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…No differences in PA were found for tumor stage, pain level or worry and depression (Table 4). Although, the Dutch study did observe an association between PA and tumor stage, 7 another study in HNC patients found an association between PA and fatigue but not with depression 12 . QoL has generally been associated with PA in HNC, but the different aspects of QoL are more or less associated 36 .…”
Section: Discussionmentioning
confidence: 93%
“…Although, the Dutch study did observe an association between PA and tumor stage, 7 another study in HNC patients found an association between PA and fatigue but not with depression. 12 QoL has generally been associated with PA in HNC, but the different aspects of QoL are more or less associated. 36 Differences in patient characteristics, sample size, study design, and methods would explain these variations in outcomes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While a pedometer is an objective method of assessing daily steps, wearing it on the waist may have underestimated upper body movements and activities such as cycling, swimming, and resistance exercise. 41 Therefore, the simultaneous use of a pedometer and a questionnaire such as the Physical Activity Scale for the Elderly (PASE) 42 is recommended to assess daily physical activity in patients with cancer. 41 Finally, biases such as those involved in selection and measurement could not be avoided.…”
mentioning
confidence: 99%
“…41 Therefore, the simultaneous use of a pedometer and a questionnaire such as the Physical Activity Scale for the Elderly (PASE) 42 is recommended to assess daily physical activity in patients with cancer. 41 Finally, biases such as those involved in selection and measurement could not be avoided. However, there are few previous reports on changes in physical activity over time in older patients with advanced NSCLC, and the results of this study are valuable in demonstrating the importance of maintaining physical activity in these patients during treatment.…”
mentioning
confidence: 99%